The Relationship Between Service Quality And Patient Satisfaction At Medika Plaza Clinic - Yolanda Datu Matarru; Asriadi; Noyumala; Normalia; Musaidah; Irma Andrianys; Gabriella Delfie Natalia (Nursing Practice Journal, 2026)
Service quality is an important factor influencing patient satisfaction with healthcare services provided by healthcare facilities. This study aims to determine the relationship between service quality and patient satisfaction at Medika Plaza Clinic. This research used a quantitative method with a cross-sectional approach. The population consisted of all patients visiting Medika Plaza Clinic, with a sample of 43 respondents selected using accidental sampling technique. Data were collected using questionnaires to measure service quality and patient satisfaction levels. Data analysis was conducted using univariate analysis to describe the frequency distribution of respondent characteristics and study variables, and bivariate analysis using the Chi-Square test to determine the relationship between service quality and patient satisfaction. The results of the Chi-Square test showed a p-value of 0.000 (p < 0.05), indicating a significant relationship between service quality and patient satisfaction at Medika Plaza Clinic.The conclusion of this study shows that service quality has a significant relationship with patient satisfaction. Therefore, improving healthcare service quality is necessary to enhance patient satisfaction. So, healthcare facilities should improve service quality across all dimensions to enhance patient satisfaction. Good service quality increases patient satisfaction, loyalty, and the positive image of healthcare facilities